Evaluación crítica de la definición legal del acoso laboral en Ecuador: perspectivas para una reforma normativa - Suárez Cabrera, María Fernanda (2024)
The research, titled “Critical evaluation of the legal definition of workplace harassment: perspectives for regulatory reform,” examines the effectiveness of Ecuadorian legislation regarding workplace harassment and proposes improvements to address its shortcomings. Although the Ecuadorian Constitution and the Labor Code establish principles to protect workers, current legislation presents significant gaps that affect the prevention and punishment of workplace harassment. Several shortcomings in current legislation were identified, including an imprecise definition of workplace harassment, a lack of clear mechanisms for reporting and resolving cases, and inadequate sanctions for those responsible. These problems contribute to a work environment where harassment can persist without appropriate consequences, negatively affecting the physical and psychological integrity of employees. The critical evaluation reveals an urgent need to review and reform existing legislation. Recommendations include clarifying the definition of workplace harassment, establishing accessible and effective reporting procedures, and creating more severe sanctions to deter inappropriate behavior. In addition, it is suggested to strengthen education and awareness about workplace harassment and ensure the implementation of preventive policies in organizations. Involving the State, the Ministry of Labor, and public institutions is crucial to improve the protection of workers' rights and promote a safe and respectful work environment.